Risk factors and effective management of preeclampsia - English FA; Kenny LC; McCarthy FP (Dove Medical Press, 2015)
Fred A English,1 Louise C Kenny,1 Fergus P McCarthy1,2 1Irish Centre for Fetal and Neonatal Translational Research (INFANT), Department of Obstetrics and Gynaecology, University College Cork, Cork, Ireland; 2Women’s Health Academic Centre, King's Health Partners, St Thomas' Hospital, London, UK Abstract: Preeclampsia, a hypertensive disorder of pregnancy is estimated to complicate 2%–8% of pregnancies and remains a principal cause of maternal and fetal morbidity and mortality. Preeclampsia may present at any gestation but is more commonly encountered in the third trimester. Multiple risk factors have been documented, including: family history, nulliparity, egg donation, diabetes, and obesity. Significant progress has been made in developing tests to predict risk of preeclampsia in pregnancy, but these remain confined to clinical trial settings and center around measuring angiogenic profiles, including placental growth factor or newer tests involving metabolomics. Less progress has been made in developing new treatments and therapeutic targets, and aspirin remains one of the few agents shown to consistently reduce the risk of developing preeclampsia. This review serves to discuss recent advances in risk factor identification, prediction techniques, and management of preeclampsia in antenatal, intrapartum, and postnatal patients. Keywords: pregnancy, treatment, risk reduction, prediction